Covert affairs. Season five [videorecording (DVD)] . - Perabo, Piper; Gorham, Christopher, 1974-; Gallagher, Peter, 1955-; Matchett, Kari; Harper, Hill, 1966- (Universal Studios, 2015)
An inexperienced CIA trainee with top-notch linguistic skills becomes a field operative under mysterious circumstances.